STUDI KERAGAMAN CENDAWAN ENTOMOPATOGEN DARI BERBAGAI RIZOSFER TANAMAN HORTIKULTURA DI KOTA PADANGSIDIMPUAN - Muhammad Agung Permadi; Rafiqah Amanda Lubis; Isrong Kinarang (Fakultas Keguruan Dan Ilmu Pendidikan, UM-Tapsel, 2019)
Entomopathogenic fungi often used as bioinsecticides to control pest insects. Entomopathogenic fungi infect through penetrating cuticles of insect or inedible. Entomopathogenic fungi can be found in the rhizosphere. The purpose of this study was to explore the types of entomopathogenic fungi in various rhizosphere of horticultural plants in Padangsidimpuan. This research was conducted at the Agrotechnology Laboratory, Faculty of Agriculture, South Tapanuli Muhammadiyah University. The results showed that the use of Tenebrio molitor as bait, can effectively obtain entomopathogenic fungi from the soil. The highest mortality of Tenebrio molitor where infected by entomopathogenic fungi was 64% on soybean plant and the lowest mortality due to infection of entomopathogenic fungi was 11% on mustard plants. There was only one genus of entomopathogenic fungi found in this study was Metarhizium sp. Keywords: soil, Metarhizium, Tenebrio molitor, infect, moist chamber